2013
DOI: 10.1160/th13-02-0174
|View full text |Cite
|
Sign up to set email alerts
|

Functional responses and molecular mechanisms involved in histone-mediated platelet activation

Abstract: Histones are highly alkaline proteins found in cell nuclei and they can be released by either dying or inflammatory cells. The recent observations that histones are major components of neutrophil extracellular traps and promote platelet aggregation and platelet-dependent thrombin generation have shown that these proteins are potent prothrombotic molecules. Because the mechanism(s) of platelet activation by histones are not completely understood, we explored the ability of individual recombinant human histones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…Plasmatic levels of nucleosomal DNA, human IL-6 and TNFα were measured using commercial ELISA kits (Cell death, ELISAPLUS Roche Diagnostic and eBioscience) and vWF levels were measured as previously described [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Plasmatic levels of nucleosomal DNA, human IL-6 and TNFα were measured using commercial ELISA kits (Cell death, ELISAPLUS Roche Diagnostic and eBioscience) and vWF levels were measured as previously described [19]. …”
Section: Methodsmentioning
confidence: 99%
“…It was reported that p38 MAPK is not important for Ca 2+ mobilization, P-selectin exposure and αIIbβ3 integrin activation in response to thrombin [150]. In contrast, recent studies showed that inhibition of extracellular signal-regulated kinases (ERK) and p38 MAPK significantly impairs P-selectin exposure and αIIbβ3 integrin activation in histone-stimulated platelets [151]. Treatment of neutrophils with platelet-activating factor (PAF) up-regulates αMβ2 integrin expression and stimulates β2 integrin-dependent adhesion through ERK, but not PI3K [152].…”
Section: Molecules Regulating the Function Of Surface Receptors Requimentioning
confidence: 99%
“…It was reported that IκBα is phosphorylated and degraded in thrombin-activated platelets and that IκB kinase inhibitors impair P-selectin exposure, αIIbβ3 integrin activation, and ERK phosphorylation in activated platelets [151, 155, 156]. Recent studies suggested that treatment of platelets with TLR2 and 4 agonists triggers P-selectin exposure through NF-κB signaling [157].…”
Section: Molecules Regulating the Function Of Surface Receptors Requimentioning
confidence: 99%
“…Even though histones have not been established as bonafide adhesion molecules, their extracellular appearance and suggested roles in this microenvironment have provoked interest in biology [21,22]. For example, a recent report indicated that extracellular histones activated a number of adhesion related signals such as PI3 kinase/Akt in platelets [23]. …”
Section: Introductionmentioning
confidence: 99%